The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3102/0034654315627499
|View full text |Cite
|
Sign up to set email alerts
|

Improving Education in Developing Countries

Abstract: In this article, we reviewed and interpreted the evidence from 223 rigorous impact evaluations of educational initiatives conducted in 56 low- and middle-income countries. We considered for inclusion in our review all studies in recent syntheses that have reached seemingly conflicting conclusions about which interventions improve educational outcomes. We grouped interventions based on their theory of action. We derived four lessons from the studies we review. First, reducing the costs of going to school and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(45 citation statements)
references
References 88 publications
3
42
0
Order By: Relevance
“…In less developed countries, there is a special situation. Thus, over the past two decades, there has been widespread reform of educational policies in these countries to increase mean years of schooling ( 26 ). Mean years of schooling is one of the components of HDI and is not considered as an indicator of development alone.…”
Section: Discussionmentioning
confidence: 99%
“…In less developed countries, there is a special situation. Thus, over the past two decades, there has been widespread reform of educational policies in these countries to increase mean years of schooling ( 26 ). Mean years of schooling is one of the components of HDI and is not considered as an indicator of development alone.…”
Section: Discussionmentioning
confidence: 99%
“…Findings by Barro and Lee (2013) reveal that the level of education around the world the globe is on the rising at an impressive rate. Similarly, Ganimian and Murnane (2016) observed that there has been a remarkable increase of higher institutions of learning in developing countries. This is also corroborated by Mahajan (2016) and Warning and Duerrenberger (2018) who posits that most developing countries especially Africa are witnessing a substantial rise in higher education enrollment.…”
Section: Introductionmentioning
confidence: 88%
“…However, most of these studies were conducted in developed regions or countries. In recent years, a growing body of evidence has suggested that merely increasing resources, such as course materials, is generally insufficient for improving student outcomes in general education in developing countries (Ganimian & Murnane, 2016;Glewwe, Hanushek, Humpage, & Ravina, 2013;Hanushek, 1997).…”
Section: Introductionmentioning
confidence: 99%